2005
DOI: 10.1203/01.pdr.0000179410.57947.88
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Fetal Kidney Development and Elevations in Arterial Blood Pressure in Young Adult Sheep after Clinical Doses of Antenatal Glucocorticoids

Abstract: Epidemiologic studies have yielded controversial information regarding an association between antenatal steroid administration and elevations in arterial blood pressure (BP). The aim of the study was to determine whether antenatal administration of a clinically relevant dose of steroids at a time when fetal nephrogenesis is at its highest results in abnormal kidney development and adult hypertension. Pregnant sheep were treated with either vehicle or betamethasone. Maternal injections were given 24 h apart at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
82
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 36 publications
(33 reference statements)
10
82
2
Order By: Relevance
“…In rats, the kidney is still immature at birth, and nephrogenesis is not complete until at least 1 wk after birth (25). Although the method of counting nephron numbers in the present study was limited compared with previous methods described (5,12), it is likely that neonatal DEX administration in the first 3 days after birth leads to reduced nephron numbers in adult life by inhibition of nephronegenesis, which has also been found in prenatal studies (14,17). In addition, in our study, DEX-treated rats had increased urinary protein loss from 8 wk onward.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In rats, the kidney is still immature at birth, and nephrogenesis is not complete until at least 1 wk after birth (25). Although the method of counting nephron numbers in the present study was limited compared with previous methods described (5,12), it is likely that neonatal DEX administration in the first 3 days after birth leads to reduced nephron numbers in adult life by inhibition of nephronegenesis, which has also been found in prenatal studies (14,17). In addition, in our study, DEX-treated rats had increased urinary protein loss from 8 wk onward.…”
Section: Discussionmentioning
confidence: 59%
“…It has been reported that maternal GC administration may lead to reduced nephron numbers in offspring (17,29). In rats, nephrogenesis is not complete until at least 1 wk after birth (25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the kidneys play a major role in the long-term regulation of arterial pressure and that change in renal function may lead to alterations in Na ϩ and water balance and blood pressure (19). In a rat model, Ortiz et al (35,36) observed that prenatal exposure to dexamethasone on days 15 and 16 of gestation induced 30 and 20% reductions in glomerular number in offspring compared with controls when assessed at 60 -70 days and 6 -9 mo of age, respectively. This reduction is possibly a consequence of dexamethasone-induced inhibition of ureteric branching morphogenesis (47).…”
mentioning
confidence: 99%
“…The dose of betamethasone administered to the ewe (0.17 mg/kg body weight) is equivalent to the 12 mg dose recommended by the National Institutes of Health consensus panel to be used in women threatened with premature labor (17). The alterations in vascular reactivity we report suggest that antenatal steroid treatment results in increased smooth muscle responsiveness and also in endothelial dysfunction, thus they could be a contributing factor for the development of hypertension (5). Limited information exists regarding the long-term effects of prenatal glucocorticoids exposure on arterial blood pressure levels in humans.…”
Section: Discussionmentioning
confidence: 79%